Transformation of the Indonesian Language Game (GABIN) Digital Assessment for Evaluating Class V Elementary Students' Paragraph Comprehension - Kristanti, Anisa; Rahmawati, Fitri Puji (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research aims to develop a Digital Assessment of Indonesian Language Games (GABIN) to evaluate paragraph comprehension among fifth-grade students. Methodology: A qualitative Research and Development (R&D) approach was employed using the ADDIE model, focusing on the Analysis, Design, and Development stages. The research subjects were fifth-grade students at Muhammadiyah Special Program Kottabarat Elementary School. Data collection techniques included observation, interviews, and documentation. Results: The research resulted in a gamification-based learning evaluation tool (GABIN) designed to assess paragraph comprehension. The tool was validated as